PLANNING AND DEVELOPING AN ONLINE ENGLISH WRITING COURSE FOR COMPUTER SCIENCE: A PRACTICAL GUIDE - Hobbs-Koch, Paul; Gahman, Paul; Rebenko, Maryna (Journal of Teaching English for Specific and Academic Purposes, 2023)
An online English course for computer science students at the B2 level was conceptualized for the E-learning institution Virtuelle Hochschule Bayern between Friedrich-Alexander University Erlangen-Nuremberg and the Technische Hochschule Nuremberg Georg Simon Ohm. The course consists of four separate modules that cumulatively target writing and language skills relevant to computer science students. Individual assessments at the end of each module serve as a review. Further, students write keystone pieces throughout the course that constitute a writing portfolio. The students’ written pieces are targeted assignments that encapsulate both the writing and the language skills addressed in each module. For instructors, these provide insight into how well students acquired the requisite skills. The writing skills cover online writing tools (COCA, AntConc, OneLook, Quillbot), software documentation, expository text based on pseudocode, and finally, summarizing/paraphrasing tools. These are reinforced through language skills that either have greater prominence in the computer science field or are frequently used for the respective writing skills. Comma and hyphen rules, maintaining objectivity in writing, describing data in figures, and embedded clauses in English are some of the language skills covered. For materials development, a combination of corpus and AI writing tools were implemented to analyse and modify authentic scientific literature. Examples, keywords, and patterns of writing taken from authentic texts were modified to create exercises relevant to topics presented in the modules. The course provides strong re natural set of writing tasks sroom.
CRIS-Team Scopus Importer:2024-12-16
Keywords: B2 online writing course; computer science and IT; writing and language skills development

Where to draw the line when the lines are blurred: A computational and functional analysis of cohesion in superhero comics - Gahman, Paul (Discourse, Context and Media, 2021)
With Halliday and Hasan's (1976) discussion of cohesion in text, linguists have long established the relation between cohesive devices employed, discursive context and register (González 2013; Guijarro 2016). However, cohesion studies in the realm of comics have largely revolved around the visual alone so far (Groensteen 2007; Kress & van Leeuwen 1996). Further, the question of how cohesive devices are employed in comics so as to attain specific discursive functions both as a reflection of the genre and as a multimodal medium remains unexplored. Based upon Halliday & Hasan's treatment of cohesion, the present research therefore addresses these deficits by examining cohesion in 20 Marvel and 21 DC modern-era comics, comprising a corpus totaling 70,865 words (tokens) and 9,805 lexemes (word types). Where cohesion was maintained, personal deixis (38.59%), endophora (12.80%), lexical repetition (11.11%) and discourse deixis (10.32%) were the most frequent (fi ≥ 10%) cohesive ties. In incohesive sentences, the cohesion breaks could be attributed to changes in narrative stage (16.85%), ellipsis (12.68%), exophora (12.08%) and so-called delayed cohesion (11.53%), whereby cohesion amongst a series of sentences is interrupted by topic digressions or prefaces beyond the discursive context but immediately re-established thereafter. These findings illuminate the multimodal interdependency between text and image in superhero comics and its effect on realizing and resolving (non–)cohesive language.
CRIS-Team Scopus Importer:2021-11-19
Keywords: Cohesion; Delayed cohesion; Discourse functions; Multimodality; Superhero comics